Investigation of Toxoplasma gondii in women with breast cancer by using the Histopathology technique in Southern Iraq - G. G. Alzaidy, Elaf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Toxoplasma gondii is an obligate intracellular protozoan parasite; it has been proposed to play a carcinogenic role in various tissue types, such as the brain tissue. This study investigates the relationship between the infection of T. gondii and breast cancer among women employing the histopathology technique. Sixty-one women participated in this study. The biopsy of breast cancer tissues was collected from a private laboratory with the support of a specialist doctor (Advisor), from December 2023 to January 2025. The examination is conducted using the histopathology technique. The histopathology technique investigation reveals that the toxoplasmosis has resulted in extensive damage to the typical breast tissues, including necrosis and tissue destruction, as well as a high density of T. gondii at the site of infection. DOI: https://doi.org/10.54633/2333-024-056-010